Assessment of Risk of Type 2 Diabetes Among Adults of Banepa Municipality, Nepal: Community Based Cross-Sectional Study - Sailendra Thapa; Pratigya Kayastha; Durga Mishra (International Journal of Travel Medicine and Global Health, 2020)
Introduction: The prevalence of type 2 diabetes has been escalating worldwide, including low- and middle-income countries such as Nepal. Early detection of individuals at risk is of the utmost importance to prevent the escalating condition. This study used a simple, cost-effective screening tool known as the Indian Diabetes Risk Score (IDRS) in order to assess the proportion of risk groups and factors associated with it among the residents of Banepa municipality, a semi-urban area of central Nepal. Methods: A community-based cross-sectional study was conducted among 245 adults of Banepa municipality. Face to face interviews were conducted to collect the information through a pretested, semi-structured questionnaire. IDRS was used to identify the risk group for developing type 2 diabetes. Data were entered in Microsoft Excel 2010 and exported to SPSS v.11.5 for further analysis. Results: The proportion of people with high risk, moderate risk and low risk was 31%, 51.4% and 17.6%, respectively for developing type 2 diabetes. The analysis showed age (P < 0.01), education (P = 0.05), marital status (P = 0.01), body mass index (BMI) (P < 0.01), waist circumference (P < 0.01), physical activities (P < 0.01) and family history of diabetes (P < 0.04) were significantly associated with risk of type 2 diabetes. Conclusion: Nearly one-third of the study participants were in high-risk group and half of them were at moderate risk. This increasing trend of risk requires an urgent application of preventive measures through lifestyle modification.